SOSIALISASI PENGEMBANGAN KAMPUNG HORTIKULTURA DI KABUPATEN PROBOLINGGO DAN LUMAJANG - Soeparjono, Sigit; Usmadi, Usmadi; Harsanti, Restiani Sih; Dewanti, Parawita; Restanto, Didik Pudji; Putri, Widya Kristiyanti (PAPUMA: Journal of Community Services, 2023)
Probolinggo and Lumajang districts are two regions in East Java that have horticultural villages with the potential to develop fruit and vegetable crops. Efforts to develop horticultural villages in the region need to be made to achieve the realization of horticultural villages that are independent and advanced, more modern and have high competitiveness. This socialization and development activity aims to increase understanding of horticultural farmer groups regarding efforts to develop horticultural villages in both regions in accordance with the standards of horticultural villages that are independent and advanced and have sales value, provide guidance and training to horticultural village farmers regarding the cultivation of horticultural plants and processing of products accordingly. commodities developed in each region, explore several factors that influence the level of success and sustainability of the horticultural village development program in the sampling area, obtain input regarding recommendations for improving programs or activities carried out in each sampling horticultural village using descriptive and quantitative analysis . Horticultural farmers' understanding regarding the development of horticultural villages in the Probolinggo and Lumajang districts is still low and does not meet the standards of horticultural villages that are independent and advanced and have sales value. Efforts to develop horticultural villages in the Probolinggo and Lumajang districts show positive developments in several commodities, while for annual fruit commodities, factors that influence the sustainability indicators of the horticultural village development program. Apart from that, there are factors such as the quality of the farmer group's human resources and the involvement of stakeholders which greatly influences the sustainability of the development of horticulture villages. Efforts to develop horticulture villages require the provision of facilities and assistance with production facilities, infrastructure and guidance on post-harvest handling, processing, market development and the development of farmers' economic institutions.